Navigating an Unclear Terrain: Challenges in Recognizing, Naming, and Accessing Services for "Forced Marriage". (July 2019) - Love, Hanna; Dank, Meredith; Esthappan, Sino; Zweig, Janine
Despite the attention forced marriage has received abroad, it remains poorly understood in the United States. This study is one of the first to examine the practice domestically, with a focus on service provision. Using interviews with those who have experienced forced marriage and relevant stakeholders, we describe challenges in recognizing, naming, and disclosing forced marriage. Findings indicate that people are unaware forced marriage services exist, face barriers to disclosing, may not identify with the term, and are reluctant to seek services. They suggest the need for training, consistent organizational definitions, inclusive terminology, programming aimed at root causes, standardized identification methods, and cultural competency.